Financing the Transition Toward Carbon Neutrality—an Agent-Based Approach to Modeling Investment Decisions in the Electricity System - Yang, Jinxi; Azar, Christian; Lindgren, Kristian (Frontiers in Climate, 2021)
Transitioning to a low-carbon electricity system requires investments on a very large scale. These investments require access to capital, but that access can be challenging to obtain. Most energy system models do not (explicitly) model investment financing and thereby fail to take this challenge into account. In this study, we develop an agent-based model, where we explicitly include power sector investment financing. We find that different levels of financing constraints and capital availabilities noticeably impact companies’ investment choices and economic performances and that this, in turn, impacts the development of the electricity capacity mix and the pace at which CO2 emissions are reduced. Limited access to capital can delay investments in low-carbon technologies. However, if the financing constraint is too relaxed, the risk of going bankrupt can increase. In general, companies that anticipate carbon prices too high above or too far below the actual development, along with those that use a low hurdle rate, are the ones that are more likely to go bankrupt. Emissions are cut more rapidly when the carbon tax grows faster, but there is overall a greater tendency for agents to go bankrupt when the tax grows faster. Our energy transition model may be particularly useful in the context of the least financially developed markets. This work should be seen as a first step towards explicitly modelling financing of the power sector.